Hydrogen peroxide induced by the fungicide prothioconazole triggers deoxynivalenol (DON) production by Fusarium graminearum. - Audenaert , Kris; Callewaert , Elien; Höfte , Monica; De Saeger , Sarah; Haesaert , Geert (Plant Breeding and Seed Science, 2020)
Fusarium head blight is a very important disease of small grain cereals with F. graminearum as one of the most important causal agents. It not only causes reduction in yield and quality but from a human and animal healthcare point of view, it produces mycotoxins such as deoxynivalenol (DON) which can accumulate to toxic levels. Little is known about external triggers influencing DON production. In the present work, a combined in vivo/in vitro approach was used to test the effect of sub lethal fungicide treatments on DON production. Using a dilution series of prothioconazole, azoxystrobin and prothioconazole + fluoxastrobin, we demonstrated that sub lethal doses of prothioconazole coincide with an increase in DON production 48 h after fungicide treatment. In an artificial infection trial using wheat plants, the in vitro results of increased DON levels upon sub lethal prothioconazole application were confirmed illustrating the significance of these results from a practical point of view. In addition, further in vitro experiments revealed a timely hyperinduction of H2O2 production as fast as 4h after amending cultures with prothioconazole. When applying H2O2 directly to germinating conidia, a similar induction of DON-production by F. graminearum was observed. The effect of sub lethal prothioconazole concentrations on DON production completely disappeared when applying catalase together with the fungicide. These cumulative results suggest that H2O2 induced by sub lethal doses of the triazole fungicide prothioconazole acts as a trigger of DON biosynthesis. In a broader framework, this work clearly shows that DON production by the plant pathogen F. graminearum is the result of the interaction of fungal genomics and external environmental triggers.